2014
DOI: 10.12968/ijtr.2014.21.4.160
|View full text |Cite
|
Sign up to set email alerts
|

A preliminary investigation of error enhancement of the velocity component in stroke patients’ reaching movements

Abstract: Background/aim: Patients with stroke who are suffering from impaired reaching movement experience insufficient spatial and temporal coordination, affecting upper limb functions and everyday life tasks. This study examines a new robot-assisted rehabilitation method for ameliorating arm reaching movements through velocity error enhancement training. The authors hypothesised that this robot-assisted rehabilitation training may encourage restoration of arm reaching abilities among post-stroke hemiparesis patients.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
28
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(30 citation statements)
references
References 45 publications
1
28
0
Order By: Relevance
“…Table 1 (EA only), Table 2 (ER only) and Table 3 (EA and ER) described all 13 studies as well as their results. Among the 13 selected studies, there are six randomized controlled trials (RCT) [ 52 57 ], five crossover studies [ 52 , 54 , 58 – 60 ], one quasi-experimental study [ 24 ], two randomized comparative study [ 61 , 62 ] and one pilot study [ 63 ]. Among all thirteen studies, only four could be found in clinical trials registry [ 52 , 56 , 57 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Table 1 (EA only), Table 2 (ER only) and Table 3 (EA and ER) described all 13 studies as well as their results. Among the 13 selected studies, there are six randomized controlled trials (RCT) [ 52 57 ], five crossover studies [ 52 , 54 , 58 – 60 ], one quasi-experimental study [ 24 ], two randomized comparative study [ 61 , 62 ] and one pilot study [ 63 ]. Among all thirteen studies, only four could be found in clinical trials registry [ 52 , 56 , 57 , 63 ].…”
Section: Resultsmentioning
confidence: 99%
“… WMFT FAS: first phase 0.51 (medium effect). second phase 0.52 (medium effect) WMFT time: First phase 0.28 (small effect) Second phase 0.14 (very small effect) 7/10, high quality Givon-Mayo et al [ 63 ] Pilot study. Trial registered NCT02017093 7 in total, E = 4 and C = 3 Ages: 45–78 (mean = 59.14 ± 9.77), 8 males and 1 female.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Moreover, researchers have recently begun to investigate a novel application of robotics [4,5] as a potential modality to enhance neuro rehabilitation that leverages the power of neuro-plasticity but using error augmentation approach [6].…”
mentioning
confidence: 99%